1997
DOI: 10.1038/sj.onc.1201202
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively spliced HPV-18 E6* protein inhibits E6 mediated degradation of p53 and suppresses transformed cell growth

Abstract: The E6 proteins originating from the tumour-associated Human Papillomavirus (HPV) types 16 and 18 have been shown to bind to and target the tumour suppressor protein, p53, for ubiquitin-mediated degradation. However, in cell lines derived from cervical neoplasias, the predominant early region transcripts are spliced and encode truncated forms of E6, termed E6*. We report here that HPV-18 E6* protein will interact both with the full-length E6 proteins from HPV-16 and HPV-18 and also with E6-AP, and subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
127
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 116 publications
(139 citation statements)
references
References 27 publications
11
127
1
Order By: Relevance
“…We have previously shown that overexpression of HPV-18 E6*I in CaSKi cells has an antiproliferative e ect, which was in marked contrast to the lack of e ect in cells which were negative for p53 and/or E6 (Pim et al, 1997). We demonstrated that this antiproliferative activity of E6*I correlated with its ability to inhibit E6 mediated degradation of p53 both in vitro and in vivo and with the subsequent increase in p53 transcriptional transactivation.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…We have previously shown that overexpression of HPV-18 E6*I in CaSKi cells has an antiproliferative e ect, which was in marked contrast to the lack of e ect in cells which were negative for p53 and/or E6 (Pim et al, 1997). We demonstrated that this antiproliferative activity of E6*I correlated with its ability to inhibit E6 mediated degradation of p53 both in vitro and in vivo and with the subsequent increase in p53 transcriptional transactivation.…”
Section: Introductionmentioning
confidence: 71%
“…We had previously shown that overexpression of HPV-18 E6*I protein has a growth suppressive e ect in CaSKi cells, but not in cells lacking p53 and/or oncogenic E6 protein (Pim et al, 1997). It has been shown previously that p53 is not Figure 4 Binding of wild-type E6*I and deletion mutants D1, D2 and D3 expressed as GST-fusions, to: (a) in vitro transcribed/ translated E6-AP; (b) in vitro transcribed/translated full-length HPV-18 E6.…”
Section: Hpv-18 E6*i Mutant D2 Is Negative For the Ability To Reduce mentioning
confidence: 99%
See 3 more Smart Citations